Urgensi Keterlibatan Wali Asuh dalam Dinamika Pendidikan di Pesantren - Alfi Najmatil Ilmy; Abd Hamid Wahid; Chusnul Muali (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2018)
Guardianship in pesantren functions to solve the decrease of effectiveness of santri’s activities along with the increase of new santri in number within modern and semi-modern pesantren. The core values of guardianship here is an innovation in pesantren to increase impact of activities and to make ease individual monitoring towards santri’s psychological and life aspects. This research implements case study approach to Pesantren Nurul Jadid located in Probolinggo Regency. Results show several strategies in the guardianship implementation in order to substitute parental roles. First, guardians act as listeners to santri in order to collect their life-aspect information. Second, guardians are individually different from those acting as pesantren daily committee member in order to provide more private approach to santri rather than a collective one. Third, guardians act as motivators, counselors, and parents for santri during their study in pesantren.